Network security in the 90's issues and solutions for managers - Madron, Thomas William 1937- (Wiley professional computing, 1992)
Using a practical approach, it explores the issues, implications and strategies behind the maintenance and management of secure electronic information systems. Coverage includes risk analysis, how much security is enough and the impact of security on performance. Along with a survey of commercially available security products, it contains a model system to demonstrate the scope of security and information integrity.